The Theology of Divine Names and Attributes: A Comparative Examination of Salafi and Ash’ari Doctrines - Muhammad Adli; Putri Rahmah Nur Hakim; Irwan Abdullah; Annisa Dwi Lestari; Tabrani ZA (Al-Albab, 2025)
This study examines the theological debate between Salafi and Ashʾari traditions regarding the interpretation of Asmāʾ wa Ṣifāt (the Divine Names and Attributes). It explores its implications for identity construction and social dynamics within contemporary Muslim communities. The research employs a qualitative approach using controversy mapping and thematic analysis of narrative data derived from religious lectures, online discussions, and relevant scholarly texts representing both theological orientations. The findings demonstrate that the debate surrounding Asmāʾ wa Ṣifāt is not merely a doctrinal disagreement but reflects a multilayered contestation involving social, epistemological, and symbolic dimensions. The literalist interpretive tendency associated with Salafi thought, and the rational-theological approach emphasized within the Ashʾari tradition, contribute to the emergence of polarization, exclusivist patterns of daʾwah, and the marginalization of moderate religious discourse in certain contexts. Moreover, the study reveals that religious interpretation functions as a social practice embedded in power relations, identity formation, and the construction of religious authority within the contemporary Muslim public sphere. By highlighting these dynamics, this research underscores the importance of interdisciplinary perspectives in understanding intra-religious theological disputes. It emphasizes the ethics of difference as an essential framework for managing diversity and reducing conflict within Muslim societies.